Using contingency valuation approaches to assess sustainable cultural heritage tourism use and conservation of the Outstanding Universal Values (OUV) at Great Zimbabwe World Heritage site in Zimbabwe - Nyasha A. Gurira; Patrick Ngulube (Elsevier, 2023)
Sustainable cultural heritage tourism is correlated to conservation use and tourism usage. The case study examines the tourism use of Great Zimbabwe World Heritage Site (GZWHS) using the contingency valuation method. It assesses whether there is enough input from tourism use directed towards the conservation of outstanding universal values (OUV). The tourism use is unsustainable, where tourism use is less than conservation use, at the property. The findings demonstrate that the plan used to maintain a balance between conservation and use at GZWHS were inadequate and unresponsive to the micro-environment in which it exists. Recommendations for a shift in conservation strategy are made.